ENZYMATIC EXTRACTION OF LOW METHOXYL PECTIN AS A POTENTIAL ANTI CANCER AGENT FROM GREEN CINCAU (Premna Oblongifolia Merr.) - Hartati, Indah; Kurniasari, Laeli (Prosiding Seminar Nasional Sains Dan Teknologi Fakultas Teknik, 2011)
Abstract Pectin is used in a number of foods as gelling agent, thickener, texturizer, emulsifier and stabilizer. It is also used in pharmaceutical, dental and cosmetic industries for its jellifying properties. Commercial pectin is divided into high and low methoxy pectin. Low methoxyl pectin (LMP) is reported posses anti cancer activity. One of our local resources, green cincau (Premna oblongifolia Merr.) is one of source of LMP. Due to its wide spectrum of functional properties and its potency as anti cancer compound, hence it is urge to develop a production process of LMP from green cincau. The current technology of pectin extraction is acidic hydrolysis. It has at leat two demerits: it does not allows pectin to be extracted fully with no damage to its structure and it does not meet the environmental safety. An enzyme-hydrolytic technology seems environmentally safe and more effective in terms of pectin yield. But nowadays the main demerits of the enzymatic extraction is the high price of commercial enzyme. In order to overcome all the demerits of pectin extraction, it is proposed to enzymatically extract the pectin of green cincau by using enzyme isolated from the local resources such as cellulase which can be isolated from hepatopancrease of snail and protease isolated from Calotropis gigantea. Key Words: enzyme, extraction, low methoxyl pectin, anti cancer, green cincau